Analisis Komparatif Pengaruh Plasticizer Gliserol dan Sorbitol Terhadap Sifat Mekanik Film Bioplastik Berbasis Kitosan: Sebuah Pendekatan Meta-Analisis - Said, Anggi Sundari Tubagus; Sari, Putri Purnama (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Chitosan bioplastics offer a sustainable alternative to synthetic packaging but suffer from inherent brittleness. This study employs a Systematic Literature Review (2015–2025) to comparatively analyze the effects of Glycerol and Sorbitol plasticizers on the mechanical properties of chitosan films. Meta-analysis results reveal a significant mechanical trade-off. Sorbitol-plasticized films demonstrate high Tensile Strength (41–75 MPa) with limited Elongation (<15%), making them suitable for rigid packaging. Conversely, Glycerol effectively enhances flexibility (Elongation up to 60%) but drastically reduces structural integrity (<25 MPa) and exhibits high hygroscopic sensitivity, positioning it as the preferred choice for flexible packaging. The study concludes that plasticizer selection must align with specific end-use requirements.